Poly(Ethylene Glycol)-Poly(Lactic Acid) TLR7 Agonist as a Novel HBsAg Immune Response Stimulant - de Liyis, Bryan; Tjandra, David Christopher; Mareska, Viona; Sutedja, Jane Carissa; Purnamasidhi, Cokorda Agung Wahyu; Krisnawadani K., Cokorde Istri Yuliandari (Family Medicine & Primary Care Review, 2023)
Hepatitis B is caused by a hepatitis B virus infection, causing inflammation of the liver. The therapeutic approach used to help treat HBV infection has been based on re-establishing a functioning T cell response and limiting additional negative consequences. Due to inadequate outcomes, new strategies for enhancing the immune response and inducing a particular HBV immune response have been developed. Activation of toll-like receptor 7 plays a role in mediating the immune response. TLR7 has shown to increase T cell activity, increase production of cytokines, increase the number of NK cells and lower serum concentrations of HBsAg, thus showing high potential to prevent and treat chronic hepatitis B. Evaluation of NK cell cytokine generation and degranu-lation reveals a considerable improvement in every cell function when compared to baseline values. However, TLR agonists are microscopic molecules that are rapidly eliminated from the system following ingestion and may cause significant systemic adverse effects. Poly(Ethylene Glycol)-Poly(Lactic Acid) can be utilised to increase the effectiveness of the toll-like receptor 7 agonist and lower the negative effects of the TLR7 agonist. TLR7 agonist distribution may be enhanced by an effective drug carrier, and conjugating a macromolecule may increase pharmacokinetics without toxicity or other negative side effects. The Poly(Ethylene Glycol)-Poly(Lactic Acid) TLR 7 agonist is potentially beneficial in treating hepatitis B as an immune response stimulant.